Perlindungan Hukum terhadap Pengusaha Sewa Menyewa Kendaraan Bermotor yang Dirugikan oleh Konsumen pada Perusahaan Paulus Rental Bike Kabupaten Badung - Philipus Dian Anjaraka; I Nyoman Putu Budiartha; Luh Putu Suryani (Jurnal Preferensi Hukum, 2020)
The development of the motor vehicle industry sector is currently growing rapidly both domestically and imported from abroad so that in this business such as manufacturers, dealers and traders of vehicles competing with each other to provide facilities to consumers in order to increase turnover trading. In this research, it discusses efforts to resolve disputes between business owners who are harmed by consumers in the non-litigation process, and analyzes the obstacles that occur in the resolution of such disputes. The method used in this study is the empirical research method. The data used are primary and secondary data. The results showed that efforts to resolve disputes between business owners, especially motor vehicle leasing when harmed by consumers, were carried out by non-litigation, namely by using an alternative dispute resolution outside the court with mediation and negotiation mechanisms to the tenants who had apologized by returning the money agreed by both parties. In addition, the inhibiting factor in efforts to resolve disputes between business owners who are disadvantaged by consumers in the dispute resolution process is the rule of law factor. In this case because the loss is classified in the civil realm, it requires time to prove the loss that must get legality from the court. Not only the rule of law, but also law enforcement factors that process cases for so long and slow respond.